2013
DOI: 10.1371/journal.pone.0072606
|View full text |Cite
|
Sign up to set email alerts
|

Viral Etiology and Clinical Profiles of Children with Severe Acute Respiratory Infections in China

Abstract: BackgroundNo comprehensive analysis is available on the viral etiology and clinical characterization among children with severe acute respiratory infection (SARI) in China during 2009 H1N1 pandemic and post-pandemic period.MethodsCohort of 370 hospitalized children (1 to 72 months) with SARI from May 2008 to March 2010 was enrolled in this study. Nasopharyngeal aspirate (NPA) specimens were tested by a commercial assay for 18 respiratory viral targets. The viral distribution and its association with clinical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
41
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 33 publications
(52 reference statements)
14
41
8
Order By: Relevance
“…RSV‐B was detected mainly in the late winter and spring months (9.52%) and in the rainy season (5.6%), in agreement with other studies [Bharaj et al, ; Seo et al, ]. Zhang et al [] reported that hMPV follows a similar seasonality pattern to RSV‐B. In our study, hMPV was detected at the highest rate during the spring (9.52%), PIV‐3 infection was mostly detected during the summer (8.51%) and Inf‐A infection peaked during the autumn season (4.08%).…”
Section: Discussionsupporting
confidence: 66%
“…RSV‐B was detected mainly in the late winter and spring months (9.52%) and in the rainy season (5.6%), in agreement with other studies [Bharaj et al, ; Seo et al, ]. Zhang et al [] reported that hMPV follows a similar seasonality pattern to RSV‐B. In our study, hMPV was detected at the highest rate during the spring (9.52%), PIV‐3 infection was mostly detected during the summer (8.51%) and Inf‐A infection peaked during the autumn season (4.08%).…”
Section: Discussionsupporting
confidence: 66%
“…In China, Zhang and others (2013) reported 54% of child SARI cases harbored HRV/HEV. 42 However, particularly for RV infections, it is reported that the infection rate is highest during the early years and decreases with age, probably due to the immunity induced by cumulative exposure to different serotypes. 43 However, the presence of a virus in the nasopharynx of a child does not necessarily mean that it is the etiological agent of the ILI; indeed, it may only represent a coincidental upper airway infection, an asymptomatic carrier state, or prolonged shedding of a pathogen that caused a previous infection.…”
Section: Discussionmentioning
confidence: 99%
“…HBoV co-infection with other respiratory viruses, including HRSV, HRV/EV, HAdV, HMPV, HPIV1e4, influenza A/B virus and HCoVs (-OC43, -229E, -NL63, -HKU1), was also screened as described previously. 20,21 Sequencing and phylogenetic analysis of HBoV1 genome Four samples of HBoV1 infection only in this study were used for complete genomes sequencing by next-generation sequencing. Samples were pretreated as previously, 22 and the amplified DNA was used as a template for Illumina Hiseq 2500 sequencing, paired-end reads (2 Â 125 bp reads) were assembled into contigs by CLC genomic workbench.…”
Section: Molecular Typing Of Hbov and Co-infection Detectionmentioning
confidence: 99%